APLIKASI PENYALUT EDIBEL BERBASIS PATI KULIT PISANG DENGAN PENAMBAHAN NATRIUM METABISULFIT PADA BUAH SALAK PONDOH KUPAS - Wirawan Wirawan; Budi Santosa (Universitas Tribhuwana Tunggadewi, 2016)
anana is a fruit that is abundant potential, In the city of Malang many processed food products such as banana chips, peanut butter and fried bananas. It results in a potential banana skin that has been utilized. To provide more benefits for the banana skin, it needs to be further processed into semi-finished products such as flour. Potential banana skin made of flour is very appropriate, because it contains 18.50% polysaccharides. This study aims to determine the concentration of starch and sodium metabisulfite banana peel right in edible coating to extend the shelf life of peeled barking. This study is to assess changes in quality of bark peeled coated starchcontaining anti-browning during storage. The research methods include the extraction of starch from banana skin and coating fruits with starch Salacca zalacca peeled banana skin anti enzymatic browning. Also the characterization of quality changes during storage barking Salacca zalacca peel. Research using a completely randomized design (CRD) are arranged with 2 factors. The first factor is starch banana peel which consists of 3 levels and the second factor namely Na-metabisulfite which consists of 3 levels with 3 replications. The results showed that the peel fruits Salacca zalacca edible coated with a coating giving the best average in all observation parameters namely water content (83.71%), acidity (0.28%), vitamin C (4:53%), texture (246.225 N)